Readiness for Discharge, Quality of Discharge Teaching, Anxiety and Depression in Surgical Patients With Cervical Cancer: A Cross-Sectional Survey - Yuan J; Zhang J; Cui X; Zhang Y; Wu Y; Xu C (Patient Preference and Adherence)
Jing Yuan,1,* Jia Zhang,1,* XiuYun Cui,1 YuTing Zhang,1 Yaru Wu,1 ChunYan Xu2 1School of Nursing, Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of China; 2Department of Gynecological Surgery, Affiliated Tumor Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: ChunYan Xu, Email xcy101413@163.comPurpose: This quantitative study aimed to determine whether the quality of discharge teaching, anxiety, depression, and various demographic and disease-related factors predict discharge readiness among cervical cancer surgical patients in Western Region of China.Methods: From November 2023 to May 2024, a convenience sampling method was employed to administer a questionnaire to cervical cancer surgery patients at a tertiary Grade A specialized hospital in Xinjiang. The survey included a patient general information questionnaire, the Quality of Discharge Teaching Scale (QDTS), the Generalized Anxiety Disorder 7-item Scale (GAD-7), a questionnaire assessing the readiness for discharge of gynecological malignant tumor surgery patients under the enhanced recovery after surgery (ERAS) model, and the Patient Health Questionnaire-9 (PHQ-9). Multivariate linear regression analysis was used to identify factors influencing discharge readiness.Results: A total of 180 cervical cancer surgery patients participated, yielding an average score of 190.46± 25.36 on the gynecological malignant tumor discharge readiness questionnaire under the ERAS model. Multiple linear regression analysis indicated that education level, chronic diseases, medication use, quality of discharge teaching, and depressive mood were significant predictors of discharge readiness of cervical cancer surgery patients.Conclusion: The overall discharge readiness of cervical cancer surgery patients was found to be at a moderate. Nurses should prioritize patients with lower education levels, chronic conditions, depression, and those requiring medication post-discharge. Personalized health guidance and targeted interventions should be developed to enhance the quality of discharge teaching, thereby improving patients’ readiness for discharge.Keywords: cervical cancer, surgery, discharge readiness, quality of discharge instructions, depression